Razvoj zaimenskega ogovornega sistema v slovenskih pisnih virih do leta 1850 - Jelovšek, Alenka (Slavistična revija, 2011)
The paper presents the development of the pronominal system of address up to 1850 as evidenced in older Slovene written sources. Separate stages are compared with the contemporary state of affairs in German and with the aid of normative sources an attempt is made to explain its typologically unexpected development in the nineteenth century.
Keywords: 16.st./1850; onikanje; purizem; Slovene; slovenščina; sporočanje; tikanje; vikanje